PENGARUH FRIM SIZE, PROFITABILITY DAN FAKTOR PENDUKUNG LAINNYA TERHADAP INCOME SMOOTHING - Fellicia Clara Angeline; Silvy Christina (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
Research of Income Smoothing is to obtain empirical evidence about the influence of firm size, profitability, financial leverage, public ownership, value of firm, institutional ownership, tax avoidance, and managerial ownership on income smoothing. Research population of this research are non financial firms that listed in Indonesia Stock Exchange from 2019 until 2021. There are 72 companies selected as a samples by using purposive sampling method. The sample are tested and analyzed using logistic regression method. Result of this research implies that firm size, profitability, public ownership, value of firm, institutional ownership, tax avoidance and managerial ownership have no significant influence toward income smoothing, while financial leverage have negative influence on income smoothing